2018
DOI: 10.15296/ijwhr.2019.20
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of the Efficacy of Panax Ginseng on Menopausal Women’s Sexual Function

Abstract: Objectives: An increase in life expectancy results in the aging population growth. This study was designed to evaluate the efficacy and adverse events of ginseng that could be used as a herbal medicine in women with sexual dysfunction. Materials and Methods: The authors of this study searched Cochrane Library, MEDLINE, Web of Science, Embase, Scopus, ProQuest, Google Scholar, and Persian databases without a time limitation until May 2018 and examined all the randomized clinical trials (RCTs) that compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Subsequently, 719 records were excluded after reviewing the titles and abstracts. The full-texts of the remaining 81 records were evaluated, and 19 studies ( Jang et al, 2008 ; Seida et al, 2011 ; Bach et al, 2016 ; Duan et al, 2018 ; Ghorbani and Mirghafourvand, 2019 ; Mohammadi et al, 2019 ; Saboori et al, 2019 ; Antonelli et al, 2020 ; Ghavami et al, 2020 ; Miraghajani et al, 2020 ; Lee et al, 2021 ; Sha’ari et al, 2021 ; Zhu et al, 2021 ; Ikeuchi et al, 2022 ; Lee et al, 2022 ; Luo and Huang, 2022 ; Naseri et al, 2022 ; Park et al, 2022 ; Zhu et al, 2022 ) were involved in the final analysis. The flow chart for the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, 719 records were excluded after reviewing the titles and abstracts. The full-texts of the remaining 81 records were evaluated, and 19 studies ( Jang et al, 2008 ; Seida et al, 2011 ; Bach et al, 2016 ; Duan et al, 2018 ; Ghorbani and Mirghafourvand, 2019 ; Mohammadi et al, 2019 ; Saboori et al, 2019 ; Antonelli et al, 2020 ; Ghavami et al, 2020 ; Miraghajani et al, 2020 ; Lee et al, 2021 ; Sha’ari et al, 2021 ; Zhu et al, 2021 ; Ikeuchi et al, 2022 ; Lee et al, 2022 ; Luo and Huang, 2022 ; Naseri et al, 2022 ; Park et al, 2022 ; Zhu et al, 2022 ) were involved in the final analysis. The flow chart for the study selection process is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…All meta-analyses were published from 2008 to 2022. These studies were published in peer-reviewed journals in eight geographical regions, including five studies each from Korea ( Jang et al, 2008 ; Bach et al, 2016 ; Lee et al, 2021 ; Lee et al, 2022 ; Park et al, 2022 ) and Iran ( Ghorbani and Mirghafourvand, 2019 ; Mohammadi et al, 2019 ; Saboori et al, 2019 ; Ghavami et al, 2020 ; Miraghajani et al, 2020 ); four from China ( Duan et al, 2018 ; Zhu et al, 2021 ; Luo and Huang, 2022 ; Zhu et al, 2022 ); and one each from Italy ( Antonelli et al, 2020 ), Canada ( Seida et al, 2011 ), Japan ( Ikeuchi et al, 2022 ), Australia ( An et al, 2011 ), and Malaysia ( Sha’ari et al, 2021 ). Eight studies had registered their protocols prior to publication ( Antonelli et al, 2020 ; Lee et al, 2021 ; Sha’ari et al, 2021 ; Zhu et al, 2021 ; Ikeuchi et al, 2022 ; Lee et al, 2022 ; Luo and Huang, 2022 ; Park et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations